2014
DOI: 10.1155/2014/191525
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Platelet-Rich Plasma (PRP) versus Autologous Whole Blood on Pain and Function Improvement in Tennis Elbow: A Randomized Clinical Trial

Abstract: Background. Autologous whole blood and platelet-rich plasma (PRP) have been both suggested to treat chronic tennis elbow. The aim of the present study was to compare the effects of PRP versus autologous whole blood local injection in chronic tennis elbow. Methods. Forty patients with tennis elbow were randomly divided into 2 groups. Group 1 was treated with a single injection of 2 mL of autologous PRP and group 2 with 2 mL of autologous blood. Tennis elbow strap, stretching, and strengthening exercises were ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 21 publications
1
37
1
1
Order By: Relevance
“…At this stage, 87 studies that did not meet the inclusion criteria were excluded. Twenty eligible RCTs were included in our network meta‐analysis (Figure ). In 13 PRP trials, the PRP preparation contained a high concentration of leukocytes in three trials and was relatively pure with deleted leukocytes in 10 trials .…”
Section: Resultsmentioning
confidence: 99%
“…At this stage, 87 studies that did not meet the inclusion criteria were excluded. Twenty eligible RCTs were included in our network meta‐analysis (Figure ). In 13 PRP trials, the PRP preparation contained a high concentration of leukocytes in three trials and was relatively pure with deleted leukocytes in 10 trials .…”
Section: Resultsmentioning
confidence: 99%
“…PRP use has hitherto been investigated in the treatment of lateral epicondylitis [6,7], knee osteoarthritis [8], hip osteoarthritis [9] patellar and Achilles tendinopathy [10][11][12], muscle injury [13] and anterior cruciate ligament injury [14]. Some studies concluded with promising outcomes that will hopefully set the new milestones of treatment options.…”
Section: Short Communicationmentioning
confidence: 99%
“…The effects of PRP treatment of lateral epicondylitis were compared with an autologous whole blood [6] and corticosteroid injections [7]: the analysis of 20 patients treated with PRP and 20 patients treated with whole blood for lateral epicondylitis showed that pain assessed by Visual Analog Scale (VAS), Mayo Elbow Performance Index, and pressure pain threshold (PPT) at 0, 4 and 8 weeks improved significantly in both populations. However, the authors indicated that 8 weeks after the treatment only the PRP group showed statistically significant improvement (P<0.05) [6]. Another analysis of lateral epicondylitis treatment considered 51 patients treated with PRP and 49 patients treated with corticosteroid injections [7].…”
Section: Short Communicationmentioning
confidence: 99%
“…The long‐lasting effects of ABPs on pain relief and functional restoration for LE have been observed in many clinical studies. Moreover, they are safe, readily available, and have a low risk of adverse effects [12‐14].…”
Section: Introductionmentioning
confidence: 99%